2002
DOI: 10.1093/emboj/cdf330
|View full text |Cite
|
Sign up to set email alerts
|

FXYD7 is a brain-specific regulator of Na,K-ATPase alpha1-beta isozymes

Abstract: P.Be Âguin and G.Crambert contributed equally to this workRecently, corticosteroid hormone-induced factor (CHIF) and the g-subunit, two members of the FXYD family of small proteins, have been identi®ed as regulators of renal Na,K-ATPase. In this study, we have investigated the tissue distribution and the structural and functional properties of FXYD7, another family member which has not yet been characterized. Expressed exclusively in the brain, FXYD7 is a type I membrane protein bearing N-terminal, post-transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
120
1
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(131 citation statements)
references
References 40 publications
(80 reference statements)
6
120
1
4
Order By: Relevance
“…Although we cannot entirely exclude that substitution of these amino acids by alanine could have some indirect effects on the global conformation of the Na,K-ATPase ␣ subunit, our results rather suggest that the predicted side of the TM9 helix of the Na,K-ATPase ␣ subunit indeed represents at least one of the interaction faces with FXYD proteins. All amino acids tested are well conserved in different Na,K-ATPase ␣ isoforms, which is compatible with the observation that after expression in Xenopus oocytes, FXYD proteins associate with all ␣ isoforms (9,17).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although we cannot entirely exclude that substitution of these amino acids by alanine could have some indirect effects on the global conformation of the Na,K-ATPase ␣ subunit, our results rather suggest that the predicted side of the TM9 helix of the Na,K-ATPase ␣ subunit indeed represents at least one of the interaction faces with FXYD proteins. All amino acids tested are well conserved in different Na,K-ATPase ␣ isoforms, which is compatible with the observation that after expression in Xenopus oocytes, FXYD proteins associate with all ␣ isoforms (9,17).…”
Section: Discussionsupporting
confidence: 87%
“…Stage V-VI Xenopus oocytes were obtained as described (24). Oocytes were injected with cRNAs coding for wild type or mutant rat Na,K-ATPase ␣1 subunits (10 ng/oocyte) or for AL1 (10 ng/oocyte) (25) or ␣1-AL1 (10 ng/oocyte) together with cRNAs for the rat Na,K-ATPase ␤1 subunit (1 ng/oocyte) or rabbit gastric H,K-ATPase ␤ subunit (1 ng/oocyte) (kindly provided by G. Sachs) with or without cRNAs coding for human FXYD2a (11), rat FXYD4 (11), or mouse FXYD7 (2 ng) (17). Oocytes were incubated in modified Barth's solution in the presence of 0.8 -1 mCi/ml [ 35 S]methionine (Easy Tag Express [ 35 S] protein labeling kit, PerkinElmer Life Sciences) at 19°C and subjected to a 6-h pulse and to 24-, 48-, and 72-h chase periods in modified Barth's solution containing 10 mM cold methionine.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the electrophoretic mobility (15 kDa) of this small protein differs significantly from the protein mass as for the other hydrophobic FXYD proteins. The previous finding that PLMS is resolved as a doublet on two-dimensional SDS-PAGE (21) could suggest that PLMS may also undergo co-or post-translational processing, as is the case for the ␥ (12, 59) and possibly also for CHIF (23) and FXYD7 (24).…”
Section: Discussionmentioning
confidence: 92%
“…Subsequent investigations by Crambert et al (22), who used a co-expression system to study the effects of mammalian FXYD1 on Na,KATPase activity, indicated that PLM interacts with and regulates Na,K-ATPase isoforms. Indeed, both FXYD 4 (CHIF) and FXYD7 have been recently reported to be tissue-specific regulators of Na,K-ATPase (23,24). Therefore, it seems conceivable that most, if not all, members of the FXYD protein family are tissue-specific regulators of Na,K-ATPase.…”
mentioning
confidence: 99%
“…6). We recently characterized FXYD7 (7), which is exclusively expressed in brain, both in neurons and glial cells. FXYD7 is subjected to Oglycosylation, which appears to be important for protein stability.…”
mentioning
confidence: 99%